(untitled) (Research, Society and Development, 2020)
Aesthetic dentistry is constantly advancing due to adhesive procedures and the development of restorative materials that seek to improve mechanical and aesthetic properties to reproduce the natural characteristics of dental structures. This study aims to highlight the clinical advantages of its use, as well as its clinical application through a literature review. The keywords "composite resins", "silicones" and "esthetics, dental" were used in the PubMed and BVS databases. The references dealing with the subjects related to the proposed theme were chosen, published between 1993 and 2020. The current composite resins make it possible to restore the shape and function with the characteristics of color, translucency and opacity similar to those of natural teeth, being indicated for recovery the harmony of the previous smile. The use of the silicone barrier to perform previous aesthetic rehabilitation facilitates the stratification process, and the aesthetic recovery of the smile as can be seen through this literature review.